Defending Oneself From Tourists: The Counter-Environmental Bubble - Cortini, Michela; Converso, Daniela (Frontiers in Psychology, 2018)
According to the Environmental Bubble Theory, tourists perform a series of strategies in order to remain anchored to their residential spots. The environmental bubble is constituted by a sort of social pellicule able to immunize tourists from the identity/cultural attacks which the visit to a foreign country implies. Such a pellicule is activated by the tourists themselves as they decide to travel in group or, for example, to eat only at the restaurants proposing their own national cuisine, and so on. Generally the potential cultural shock of residents is not taken into consideration in literature, even if it is plausibile to make the hypothesis of a counter-environmental bubble performed by the residents in order to defend their own culture and their identity from the attacks of mass tourism, especially for cities that live on tourism, as, for example, Florence or Siena do. Our study aims at testing the access to local tradition made available in promotional material. The hypothesis we propose is that there should exist a difference in promoting cultural heritage and intimate culture. The intimate culture refers to the living culture, the way of living, comprehending cuisine, education, religion, the way by which the role of females and males are performed, and so on. On the other hand, the cultural heritage, or historical culture, makes reference to a culture meant as belonging to the whole mankind, as it happens, for example, for archeological sites or museums. In more detail, we propose the hypothesis that the intimate culture is maintained unaccessible for tourists' gaze, or at least accessible only in the shape of a spectacularized event, the so called pseudo-event of Boorstin. Using the software NUD*IST we analyzed the promotional material of the city of Siena. Our results confirm Boorstin's theory about pseudo-events realized for tourists. The difference between cultural heritage and intimate culture promotion we have revealed shows an additional lecture of the Boorstinian framework, which makes an echo to the environmental bubble theory (Cohen, 1972), stressing the risk in terms of social and cultural identity tourism implies for both residents and tourists.